2012
DOI: 10.1063/1.4714721
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties and electrical conduction of high-k LaGdO3 ceramics

Abstract: The temperature and frequency dependent dielectric properties and leakage conduction mechanism in LaGdO3 (LGO) ceramics have been studied, and this material has been identified as a potential high-k candidate for the future complementary metal-oxide-semiconductor (CMOS) and dynamic random access memory (DRAM) technology nodes. The dielectric constant and the loss tangent at 100 kHz were ∼21.5 and ∼0.003, respectively, at ambient conditions without any significant temperature and voltage dependence. The ac cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…In the temperature range (>T t ) the Arrhenius plots show a linear variation and the estimated activation energy values (Fig. 8) in the range E a = 1.04-1.16 eV are in agreement with earlier studies [39][40][41] and correspond to the migration of doubly ionized oxygen vacancies (Vö). In the Aurivillius family of oxides the major contribution to the electrical conductivity originates due to the loss of bismuth.…”
Section: And Ac Conductivitysupporting
confidence: 86%
See 1 more Smart Citation
“…In the temperature range (>T t ) the Arrhenius plots show a linear variation and the estimated activation energy values (Fig. 8) in the range E a = 1.04-1.16 eV are in agreement with earlier studies [39][40][41] and correspond to the migration of doubly ionized oxygen vacancies (Vö). In the Aurivillius family of oxides the major contribution to the electrical conductivity originates due to the loss of bismuth.…”
Section: And Ac Conductivitysupporting
confidence: 86%
“…At higher temperatures (T P 150°C) variation in r ac (T) shows a frequency independent plateau in the low frequency range <1 kHz, whereas at higher frequencies (>1 kHz), r ac is frequency dependent with reduced dispersion. The observed frequency and temperature dependence in r ac could be fitted well to a double power law [40,45,46].…”
Section: And Ac Conductivitymentioning
confidence: 76%
“…The equivalent breakdown field deduced from the slope of this plot was about $36 MV/cm which comes out to be $6 MV/cm [breakdown field, E BD ¼ equivalentfield=ðk=3:9Þ] by considering the permittivity of LGO (k $ 22). 10 This experimental value is comparable with the theoretical value obtained (5.5 MV/cm) by applying the "square root" rule in accordance with the thermo-chemical/molecular model 26 for the break down field E BD ¼ 29:9e À0:55 r . The maximum energy storage density calculated using the relation W ¼ ðe 0 e r E 2 BD =2Þ was around 40 J/cm 3 , and this higher figure may be of particular interest for energy density capacitor applications in energy storage and power compression devices.…”
supporting
confidence: 85%
“…We have recently shown that amorphous LaGdO 3 (LGO) a ternary high-k dielectric oxide material with high and linear dielectric constant of ~22, large band gap, good thermal stability, and high crystallization temperature of ~ 1000 °C is promising material for CMOS devices [3]. In this paper we report, to the best of our knowledge for the first time, the growth of RRAM devices based on amorphous thin films of LGO in Pt/ LGO/ Pt stack geometry, their unipolar resistive switching characteristics and associated conduction behaviors in both the low resistance state (LRS) and high resistance states (HRS).…”
Section: Introductionmentioning
confidence: 99%